Testing the Mystic School Mobile Application to Promote Active Commuting to School in Spanish Adolescents: The PACO Study - Romina Gisele Saucedo-Araujo; Francisco Javier Huertas-Delgado; Yaira María Barranco-Ruiz; Isaac José Pérez-López; Susana Aznar-Laín; Palma Chillón; Manuel Herrador-Colmenero (MDPI AG, 2022)
Active commuting to and/or from school (ACS) is an opportunity to increase daily physical activity (PA) levels in young people. Mobile-device interventions focused on promoting the practice of health-related PA can be more cost-effective than traditional interventions in this population. Objective: To analyze the adolescents' opinion of the mobile application (app) Mystic School, which was designed to promote ACS in Spanish adolescents. Methods: A total of 44 students (14-15 years old) from Granada and Jaén participated in the test of the Mystic School app during two phases: phase 1 (n = 10) for 2 weeks and phase 2 (n = 34) for 1 month. Each phase included an app presentation, a follow-up, and focus group sessions. The qualitative analysis was carried out through NVivo software. Results: In phase 1, adolescents reported improvements in the design and functioning, such as the avatar movement, virtual steps utilities, and multiplayer function. These suggestions were included in phase 2. After phase 2, adolescents reported that it is important to add the possibility of playing without an Internet connection to the game, to include more competitive options, prizes, and to increase the difficulty of the levels. In both phases, problems with the step number counting remained. Conclusion: The Mystic School app can be a useful tool for the physical education teacher to integrate the content from this curriculum related to the promotion of PA, such as ACS.